Active case finding among marginalised and vulnerable populations reduces catastrophic costs due to tuberculosis diagnosis. Issue 1 (1st January 2018) - Shewade, Hemant Deepak; Gupta, Vivek; Satyanarayana, Srinath; Kharate, Atul; Sahai, K.N.; Murali, Lakshmi; Kamble, Sanjeev; Deshpande, Madhav; Kumar, Naresh; Kumar, Sunil; Pandey, Prabhat; Bajpai, U.N.; et al.
ABSTRACT: Background : There is limited evidence on whether active case finding (ACF) among marginalised and vulnerable populations mitigates the financial burden during tuberculosis (TB) diagnosis. Objectives : To determine the effect of ACF among marginalised and vulnerable populations on prevalence and inequity of catastrophic costs due to TB diagnosis among TB-affected households when compared with passive case finding (PCF). Methods : In 18 randomly sampled ACF districts in India, during March 2016 to February 2017, we enrolled all new sputum-smear-positive TB patients detected through ACF and an equal number of randomly selected patients detected through PCF. Direct (medical and non-medical) and indirect costs due to TB diagnosis were collected through patient interviews at their residence. We defined costs due to TB diagnosis as 'catastrophic' if the total costs (direct and indirect) due to TB diagnosis exceeded 20% of annual pre-TB household income. We used concentration curves and indices to assess the extent of inequity. Results : When compared with patients detected through PCF ( n = 231), ACF patients ( n = 234) incurred lower median total costs (US 4.6 and 20.4, p < 0.001). The prevalence of catastrophic costs in ACF and PCF was 10.3 and 11.5% respectively. Adjusted analysis showed that patients detected through ACF had a 32% lower prevalence of catastrophic costs relative to PCF [adjusted prevalence ratio (95% CI): 0.68 (0.69, 0.97)]. The concentration indices (95% CI) for total costs in both ACF [−0.15 (−0.32, 0.11)] and PCF [−0.06 (−0.20, 0.08)] were not significantly different from the line of equality and each other. The concentration indices (95% CI) for catastrophic costs in both ACF [−0.60 (−0.81, –0.39)] and PCF [−0.58 (−0.78, –0.38)] were not significantly different from each other: however, both the curves had a significant distribution among the poorest quintiles. Conclusion : ACF among marginalised and vulnerable populations reduced total costs and prevalence of catastrophic costs due to TB diagnosis, but could not address inequity.